Concept maps as a didactic strategy for learning of concepts of cell biology in students of health sciences (2009)
For students of health sciences, knowledge of biology is a cornerstone to successfully face the challenges presented to them related to this field of knowledge and to interpret specific phenomena of medical science and health. This paper shows the results of the use of the concept maps for meaningful learning of cellular biology concepts. Objective: to determine the effectiveness of the concept maps as a didactic strategy in the learning of concepts of cellular Biology in students of Health Sciences. Material and methods: It was worked with a cuasi-experimental design of pre-test and post-test with two intact groups: an experimental group (it used the concept maps as learning strategy) and a control group (it did not use the concept maps as learning strategy). The students were evaluated using a pre-test and post-test, built with multiple-choice questions with one answer in the levels of knowledge, comprehension and analysis of the cognitive domain of Bloom's Taxonomy. Results: In the post-test found no significant differences in the total number of questions. However significant differences were found between groups in the application level, observing better results in the experimental group. Conclusions: The concept maps gave students a tool to learn concepts of cell biology significantly. However, its effective use depends on factors such as motivation for learning, continuous training in mapping, significant contents of learning and implementation time.